Analisis Pengaruh Electronic Word Of Mouth Terhadap Minat Beli Produk Kosmetik Maybelline Dengan Brand Trust Sebagai Variabel Mediasi (Studi Kasus Pada Pengguna Aplikasi Online Shop LAZADA.co.id) - Sariati Mudarifah (PRAGMATIS, 2020)
This research aims to find out the effect of electronic word of mouth on buying interest in Maybelline cosmetics products to users of the LAZADA.Co.Id online shop application with brand trust as a mediating variable. The approach used in this study uses a quantitative approach. Sampling in this study uses the method of puposive sampling, which is sampling with certain considerations. The sample of this study amounted to 100 respondents who knew Maybelline cosmetics produscts and had or had used the online shop LAZADA.Co.Id app more or less in the last 3 months. Collecting data was conducted by distributing questionnaires online through google form. Processing data in this study using SPSS 17 and website http://quantpsy.org/sobel/sobel.htm. Data analysis techniques of respondents used multilevel regression analysis and sobel test. The results of this study indicate the first hypothesis is accepted, the second hypothesis is accepted, the third hypothesis is accepted, and the fourth hypothesis is accepted. And the conclusion of the influence of brand trust variables as mediating variabels on the relationship between electronic word of mouth variables on buying interest variables.